Zonas y modos de intersección: el “yo-narrador-investigador” y el relato de la investigación - Annick Louis (Cuadernos LIRICO)
The 21st century has seen an increase in the production of narratives that blur the boundaries between fiction and non-fiction, which I propose to call “crossing-border narratives”, since they transform the dividing line between these two types into a vast narrative territory. In this category, the “investigation narrative” occupies a special place due to its success with critics and audiences alike. In this article, we examine the way in which the “I-narrator-investigator” is articulated to the investigative narrative, as well as the reading effects generated by each of these modalities.